Investigation of the antioxidant effects of pheniramine maleate and nebivolol on testicular damage in rats with experimentally induced testis torsion - Yuvanc,Ercan (2018)
Abstract Purpose: To investigate the biochemical, histopathologic, and spermatogenetic changes in the detorsionated testicle after experimental torsion and to study the antioxidant effects of pheniramine maleate and nebivolol. Methods: Twenty-four Sprague-Dawley male rats were divided into 4 groups: Group 1: Sham; Group 2: Torsion/Detorsion (T/D); Group 3: T/D + Pheniramine maleate (PM); Group 4: T/D + Nebivolol (NB) group. Paroxanase (PON), total antioxidant status (TAS), total oxidant status (TOS), and oxidative stres index (OSI) were measured, and spermatogenetic and histopathologic evaluation was performed in tissue and blood samples. Results: The evaluation of tissue TAS indicated no statistically significant difference in Group 3 compared to Group 2. A statistically significant increase was detected in Group 4 compared to Group 2. Serum PON levels revealed a statistically significant increase in Groups 3 and 4 compared to Groups 1 and 2. The Johnsen testicular biopsy score decreased in Groups 3 and 4, but the decrease was not statistically significant. Conclusions: Pheniramine maleate and nebivolol have antioxidant effects against ischemia-reperfusion damage. They also support tissue recovery, which is more significantly observed by nebivolol.